2006
DOI: 10.1002/ca.20220
|View full text |Cite
|
Sign up to set email alerts
|

Soft tissue connection between rectus capitus posterior minor and the posterior atlanto-occipital membrane: A cadaveric study

Abstract: This investigation determined the variation, prevalence, tissue-type, and sex bias in the soft-tissue bridge between rectus capitis posterior minor (RCPMi) and the posterior atlanto-occipital membrane (PAO). Seventy-five cadavers (27 females and 48 males) were surveyed. When RCPMi was revealed, its superior attachment was detached and the muscle was reflected inferiorly to determine if it was attached to the underlying PAO. If a soft-tissue bridge was identified, the fibers found within the bridge were classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 5 publications
(7 reference statements)
0
29
0
2
Order By: Relevance
“…Hack et al 36 found the existence of a connective tissue bridge between the RCPmin muscle and the dorsal spinal dura at the C0 -C1 junction, providing anatomic evidence to link the two disparate tissues. This muscle attachment to the cervical spine dura was later confirmed by Humphreys et al 37 and Zumpano et al 38 It is unknown whether this anatomic feature of the RCPmin muscle could make it more sensitive to atrophy than RCPmaj.…”
Section: Discussionmentioning
confidence: 83%
“…Hack et al 36 found the existence of a connective tissue bridge between the RCPmin muscle and the dorsal spinal dura at the C0 -C1 junction, providing anatomic evidence to link the two disparate tissues. This muscle attachment to the cervical spine dura was later confirmed by Humphreys et al 37 and Zumpano et al 38 It is unknown whether this anatomic feature of the RCPmin muscle could make it more sensitive to atrophy than RCPmaj.…”
Section: Discussionmentioning
confidence: 83%
“…Many anatomical studies have focused on the connections of RCPmi in the past (Hack et al;Rutten et al;Yuan et al;Alix & Bates;Elliott et al, 2005;Zumpano et al, 2006;Hallgren, 2014;Hallgren et al, 2014;Scali et al, 2015), while few studies were related to the morphological parameters of the RCPmi. In this study, a quantitative MRI measurement of the RCPmi was developed and a reference value of imaging anatomical parameters of the RCPmi was set up.…”
Section: Discussionmentioning
confidence: 99%
“…27,68,85 A study conducted by Hack et al 27 reported the presence of a connective tissue bridge joining the rectus capitis posterior minor muscle to the spinal dura in all cadaveric specimens. Zumpano and associates 90 found this connective tissue bridge to be present in 67% of cadavers, indicating that this represents normal anatomy rather than a rare anatomical anomaly. Nash et al, 49 expanding on these studies, reported that the PAO membrane is actually composed of the deep fascia of the rectus capitis posterior minor muscle and the vertebral vascular sheath.…”
Section: Anatomymentioning
confidence: 92%
“…77 This structure has been noted by several authors to extend laterally over the atlantooccipital joint capsules. 90 The PAO membrane runs adjacent to the rectus capitis posterior minor posteriorly and the dura mater anteriorly. Several authors have noted connection or interdigitation of the PAO membrane with both the rectus capitis posterior minor muscle and the spinal dura mater.…”
Section: Anatomymentioning
confidence: 99%
See 1 more Smart Citation